Analyzing Startup Financing Models In Indonesia: A Bibliometric Study - Elwisam; Digdowiseiso , Kumba; Yartono , Nungki (CV ODIS, 2023)
This research uses bibliometric analysis to investigate research developments related to startup financing models in Indonesia from 2016 to 2023. Bibliographic data was obtained through Semantic Scholar with the key term